Identification of positively selected genes in human pathogenic treponemes: Syphilis-, yaws-, and bejel-causing strains differ in sets of genes showing adaptive evolution. - Denisa Maděránková; Lenka Mikalová; Michal Strouhal; Šimon Vadják; Ivana Kuklová; Petra Pospíšilová; Lenka Krbková; Pavlína Koščová; Ivo Provazník; David Šmajs (Public Library of Science (PLoS), 2019)
Background Pathogenic treponemes related to Treponema pallidum are both human (causing syphilis, yaws, bejel) and animal pathogens (infections of primates, venereal spirochetosis in rabbits). A set of 11 treponemal genome sequences including those of five Treponema pallidum ssp. pallidum (TPA) strains (Nichols, DAL-1, Mexico A, SS14, Chicago), four T. p. ssp. pertenue (TPE) strains (CDC-2, Gauthier, Samoa D, Fribourg-Blanc), one T. p. ssp. endemicum (TEN) strain (Bosnia A) and one strain (Cuniculi A) of Treponema paraluisleporidarum ecovar Cuniculus (TPeC) were tested for the presence of positively selected genes. Methodology/principal findings A total of 1068 orthologous genes annotated in all 11 genomes were tested for the presence of positively selected genes using both site and branch-site models with CODEML (PAML package). Subsequent analyses with sequences obtained from 62 treponemal draft genomes were used for the identification of positively selected amino acid positions. Synthetic biotinylated peptides were designed to cover positively selected protein regions and these peptides were tested for reactivity with the patient's syphilis sera. Altogether, 22 positively selected genes were identified in the TP genomes and TPA sets of positively selected genes differed from TPE genes. While genetic variability among TPA strains was predominantly present in a number of genetic loci, genetic variability within TPE and TEN strains was distributed more equally along the chromosome. Several syphilitic sera were shown to react with some peptides derived from the protein sequences evolving under positive selection. Conclusions/significance The syphilis-, yaws-, and bejel-causing strains differed relative to sets of positively selected genes. Most of the positively selected chromosomal loci were identified among the TPA treponemes. The local accumulation of genetic variability suggests that the diversification of TPA strains took place predominantly in a limited number of genomic regions compared to the more dispersed genetic diversity differentiating TPE and TEN strains. The identification of positively selected sites in tpr genes and genes encoding outer membrane proteins suggests their role during infection of human and animal hosts. The driving force for adaptive evolution at these loci thus appears to be the host immune response as supported by observed reactivity of syphilitic sera with some peptides derived from protein sequences showing adaptive evolution.